Validade dos critérios eletrocardiográficos clássicos para o diagnóstico de hipertrofia ventricular esquerda em gestantes: comparação com a massa ventricular esquerda ao ecocardiograma - Eder Tadeu Criscuolo Gabriel (2007)
This dissertation, composed of two articles, studies the value of theelectrocardiography as a method of diagnosis of the left ventricular myocardial hypertrophy (LVH), using, as gold-standard, the left ventricular mass determined by echocardiography. In the first article, we revised of the main criteria of the electrocardiography described for the LVH diagnosis. In this manner, a bibliographic research was carried out inthe Medline and Lilacs database, from 1980 to 2005. For situations of screening for LVH, the RV6 / RV5 voltage ratio > 0,65 has presented good results in relation to the sensibility (89%), but it has shown low specificity (21%). The Cornell voltage criterion has presented good results when applied to female individuals and in population with body mass index above the values considered normal. The Sokolow-Lyon-Rappaport criterion has presented better sensibility when applied to male individuals (73,53%), but has shown low diagnostic specificity (40,63%). The various electrocardiographic criteria have presented great differences of sensibility and specificity in dependence of factors, such as: nature of the pathologies, age group, biotype, habits of life, and population groups. We concluded that an ideal electrocardiographic criterion which presents high sensibility and high specificity indifferent clinical conditions presented by patients it is not available yet.In the second article, the sensibility, specificity, positive predictive value, negative predictive value, and the accuracy of nine electrocardiographic criteria for the diagnosis of LVH in 40 pregnant women with chronic systemic arterial hypertension and in 40 pregnant women who are normotensive, all of them in the third trimester of pregnancy, were analyzed, using, as gold-standard, the left ventricular mass determined by the echocardiography. The cut off points considered for the echocardiographic diagnosis of left ventricular hypertrophy in pregnant women were 110,4g/m2 e 122,38g/m2. The nine electrocardiographic criteria analyzed were: Sokolow-Lyon (the highest R wave in lead V5 or V6 plus S wave in lead V1 > 35mm); Sokolow-Lyon-Rappaport (the highest R wave in lead V5 or V6 plus S wave in lead V2 > 35mm); Cornell (Sum of the amplitudes of the R wave in lead aVL and the S wave in lead V3 > 20mm); R wave in lead aVL > 11mm; Gubner (R wave in lead DI plus S wave in lead DIII > 25mm); Lewis [(R wave in lead DI - S wave in lead DI) (R wave in lead DIII S wave in lead DIII)] > 17mm; Grant (S wave in lead V1 or V2 plus R wave in lead V6 > 40mm); Romhilt Estes point-score > 5 points; Ratio between R wave voltage in lead V6 andV5 > 1. When using the values above 110,4 g/m2 for the echocardiographic diagnosis of left ventricular hypertrophy in pregnant women, the RV6 / RV5 voltage ratio > 1 has presented 25% of sensibility, the best of the group, but it has presented the lowest specificity (78%), a positive predictive value of only 22%, and the smallest accuracy among the nine analyzed criteria. However, when using of the values above 122,38 g/m2 for the echocardiographic diagnosis of left ventricular hypertrophy in pregnant women, the RV6 / RV5 voltage ratio > 1 has shown 33% of sensibility, and along with Sokolow-Lyon-Rappaport were the only criteria of the group to present detectable sensibility for the LVH diagnosis, although RV6/RV5 voltage ratio >1 still demonstrates the lowest specificity and accuracy among all the analyzed criteria. We concluded, in this way, that the nine electrocardiographic studied criteria have shown low sensibility for the LVH diagnosis, and only Sokolow-Lyon-Rappaport criterion has presented statistical value to be utilized in LVH diagnosis, in pregnant women, who are hypertensive, in the third trimester of pregnancy.